THE IMPLEMENTATION OF SETTLEMENT SERVICES AND DISTRIBUTION IN GUIDANCE AND COUNSELING - Sestuningsih MR (PROSIDING SEMINAR KIMIA, 2015)
The purpose of this research is to find out the implementation of settlement services and distribution on students of class IX of public Junior High School (SMPN) 22 Samarinda. This research is a descriptive qualitative where the focus of the research is the implementation of settlement services and distribution. Method of data collecting uses interview, observation and documentation technique. The technique of data analysis of the research consists of four components namely data collecting, data simplifying, data description and conclusion. The result of this research argues that implementation of settlement services and distribution on student of grade IX of SMP N 22 Samarinda has been comprehensively and appropriately conducted in accordance with the programs.